2013
DOI: 10.1097/gme.0b013e31826e7649
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sleep quality and correlates in a large cohort of Colombian women around menopause

Abstract: Despite study limitations, poor sleep quality is highly prevalent in this large middle-aged Colombian female sample and is related to menopausal symptom severity, tobacco use, and presence of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
3
26
0
3
Order By: Relevance
“…Few reports supported our findings both in healthy population and in dialysis patients. 33,34 In contrast, two studies in PD patients indicated that age might influence sleep quality. 30,35 The mixed results regarding the effects of age on sleep quality may be attributed to the differences in the study populations and measurement tools.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports supported our findings both in healthy population and in dialysis patients. 33,34 In contrast, two studies in PD patients indicated that age might influence sleep quality. 30,35 The mixed results regarding the effects of age on sleep quality may be attributed to the differences in the study populations and measurement tools.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kuh et al (9) in the UK with over 1200 women, the risk of sleep disturbances relative to that among premenopausal women was higher by a factor of 1.5 for perimenopausal women and a factor of 3.4 for postmenopausal women. The prevalence of sleep difficulty varies between 14% and 53% in the menopausal period (9)(10)(11). In Timur and Sahin's study (12) of 887 women in the menopausal period carried out in Malatya, Turkey, the prevalence of sleep difficulty was found to be 54%.…”
Section: Discussionmentioning
confidence: 99%
“…Se encontró que el 61,8% informaron no conseguir dormir las horas necesarias, 56,1% que aunque dormían no descansaban y 49,7% desde la levantada estaban cansadas. Cifras similares a las señaladas por otros autores con otras herramientas, lo que permite señalar que la mitad de las mujeres climatéricas tienen percepción de mal dormir, condicionante para deterioro de la CV así como factor de riesgo asociado a algunas enfermedades crónicas, especialmente cardiovascular con impacto en la morbilidad e incluso mortalidad (22)(23)(24). En un estudio a gran escala en 1.078 mujeres colombianas, edad 40-59 años, siendo 86,1% mestizas y 13,9% afrocolombianas, valoradas con el Índice de Calidad del Sueño de Pittsburgh, se estimó prevalencia de mala calidad del sueño del 57,1% (24).…”
Section: Discussionunclassified
“…Relación de pareja. Cada pregunta es una manifestación de salud, que se responde tipo Likert: 0 (no presente), 1-2-3-4 (estados intermedios) y 5 (mucho), siendo de mejor a peor en las preguntas negativas [1,2,3,5,6,7,9,10,11,12,14,16,17,18,19,21,23,24,25,27,28,29,31] y lo contrario en las positivas [4,8,13,15,20,22,26,30]. Las sumas crean el puntaje de los dominios y entre estos el global, que va de 0-155.…”
Section: Cavimec [Calidad De Vida En La Menopausia Y Etniasunclassified